2018
DOI: 10.1177/2055207618779714
|View full text |Cite
|
Sign up to set email alerts
|

Seeking connectivity to everyday health and wellness experiences: Specificities and consequences of connective gaps in self-tracking data

Abstract: ObjectiveSelf-tracking technologies have created high hopes, even hype, for aiding people to govern their own health risks and promote optimal wellness. High expectations do not, however, necessarily materialize due to connective gaps between personal experiences and self-tracking data. This study examines situations when self-trackers face difficulties in engaging with, and reflecting on, their data with the aim of identifying the specificities and consequences of such connective gaps in self-tracking context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
(73 reference statements)
0
9
0
Order By: Relevance
“…When self-tracking devices are to social networks, the proportion of lower-performing friends may positively influence users’ physical activities [ 56 ]. Moreover, Yli-Kauhaluoma and Pantzar [ 87 ] examined the gap between individual experiences and self-tracking data. They found that individuals always feel upset and confused when comparing invisible or inaccurate personal health data with their daily experiences and may eventually refuse to use self-tracking devices.…”
Section: Resultsmentioning
confidence: 99%
“…When self-tracking devices are to social networks, the proportion of lower-performing friends may positively influence users’ physical activities [ 56 ]. Moreover, Yli-Kauhaluoma and Pantzar [ 87 ] examined the gap between individual experiences and self-tracking data. They found that individuals always feel upset and confused when comparing invisible or inaccurate personal health data with their daily experiences and may eventually refuse to use self-tracking devices.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike traditional health literacy programs that focus on delivering general health knowledge [ 39 , 51 ], specific information related to an individual’s own health data can be easier to understand because it is tied to their own health concerns. However, we must keep in mind that interpretation of automatically tracked data is sometimes unreliable or may even cause misunderstandings [ 52 , 53 ]. For example, sleep tracking apps using pressure sensors to estimate sleep hours can cause false-positive detections when people are performing other activities in bed [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, because patients are not medical experts, they could not always tell which data are relevant to their health, especially if they kept track of various types of data. Although our work did not examine clinicians’ perspectives on PGD sharing, previous work has found that clinicians are also concerned about the time they need to review PGD in the clinic [ 6 , 60 ] and may even consider these data to be distracting [ 52 ]. To resolve the dilemma of clinicians having limited time and patients feeling uncertain about whether their personal health data can be helpful, an approach should be developed to help patients share their data efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…However, because patients are not medical experts, they could not always tell which data are relevant to their health, especially if they kept track of various types of data. Although our work did not examine clinicians' perspectives on PGD sharing, previous work has found that clinicians are also concerned about the time they need to review PGD in the clinic [6,60] and may even consider these data to be distracting [52].…”
Section: The Gaps Between Tracking and Sharing Pgdmentioning
confidence: 99%
“…Unlike traditional health literacy programs that focus on delivering general health knowledge [39,51], specific information related to an individual's own health data can be easier to understand because it is tied to their own health concerns. However, we must keep in mind that interpretation of automatically tracked data is sometimes unreliable or may even cause misunderstandings [52,53]. For example, sleep tracking apps using pressure sensors to estimate sleep hours can cause false-positive detections when people are performing other activities in bed [53].…”
Section: Reflecting On the Relationships Between Pgd Tracking And Health Literacymentioning
confidence: 99%